A method for estimating stress-strain history in cement-based composites and calcite particle aggregates
By burying calcium stone particles as stress sensors in structural materials and measuring stress history by using double crystal density changes, the problem of stress history measurement in materials with different elastic modulus is solved, simple and accurate stress history measurement is achieved, and the reliability of structural safety assessment is improved.
Patent Information
- Application Number
- JP2022535388
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-09
- Filing Date
- 2021-07-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-07-08
AI Technical Summary
The prior art is difficult to effectively measure stress history in structural materials with different elastic modulus, and traditional methods rely on human judgment and external sensors, which have problems of unreliability and practicality.
By burying multiple calcium stone particles in the structural material as stress sensors, and measuring stress history using the bicrystal density changes of these particles, combining prefabricated cement-based materials and non-shrinkable mortars to ensure the reliability and wide applicability of the measurement.
It realizes simple and effective measurement of stress history in structural materials with different elastic modulus, avoids the unreliability of traditional methods and the impact of external sensors on the material, and improves the accuracy of structural safety assessment.
Smart Images

Figure 0007658598000001 
Figure 0007658598000002 
Figure 0007658598000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for estimating the stress-strain history in a cement-based composite material and to a calcite particle aggregate. [Background technology]
[0002] In order to evaluate the stress and damage that has occurred in structural materials that are mainly made of cement, a method is used in which inferences are made from hammering sounds and cracking sounds, but this method relies on human intuition and experience and is not very reliable.
[0003] Concrete structural materials may be subjected to temporary large external forces due to natural disasters such as earthquakes, tornadoes, and typhoons, or accidents such as transportation collisions. In such cases, if the structural material does not break but only deforms within its elastic limit, it will return to its original state after the external force is released, and it is not possible to accurately determine the magnitude of force the structural material received, or what kind of stress was generated in which part.
[0004] Known methods for measuring internal stress in structural materials include placing markers or sensors in the structural material in advance to measure the existing stress, or taking a core and estimating the stress from the amount of rebound or the AE Kaiser effect (the generation of elastic waves when deformation is caused by external forces or when micro-fracture occurs).
[0005] In assessing the safety of concrete structures, it is important to know what kind of stress has occurred in the structural material, and for that purpose, it is conceivable to obtain the stress history by installing strain sensors on the surface of the concrete material and monitoring it constantly. However, it is not realistic to carry out such monitoring for a long period of time for general structures such as buildings, bridges, and tunnels. In addition, electrical sensors are foreign bodies to such structural materials, and it is conceivable that they will have mechanical properties different from those of the original structural materials.
[0006] For this reason, if structural materials themselves could be given the ability to record paleostresses, and measurements could be taken when necessary to gain knowledge about large stresses that occurred in structural materials in the past, it is believed that this would greatly contribute to the safety assessment of structures, and technologies to achieve this have been proposed.
[0007] Patent Document 1 discloses a method for measuring stress history by repeatedly detecting the Kaiser effect by clamping a concrete specimen between pressure plates and applying a load exceeding the past stress history. Patent Document 2 discloses a method for measuring the stress history of a test object that contains calcite particles and can be elastically deformed by receiving an external force, based on the change in twin density of the calcite particles after receiving the external force.
[0008] Patent document 3 discloses a method for measuring the stress history of a test object having a large number of calcite particles embedded therein and capable of elastically deforming under external force, based on the proportion of calcite particles that have undergone twin deformation after being subjected to an external force. This technique is an improvement over the technology of Patent document 2, which can be applied under low stress conditions.
[0009] Non-Patent Document 1 is related to Patent Document 2, and discloses a method for finding a relationship in which twin density is proportional to differential stress from the results of compression tests on sandstone specimens, and for calculating the stress-strain relationship from a simulation of virtual rocks using the distinct element method (DEM). Patent Document 4 discloses a technique for synthesizing calcite particles required for the verifications in Patent Documents 2 and 3 and Non-Patent Document 1.
[0010] In methods that use the Kaiser effect, such as that in Patent Document 1, cracks are generated by applying a load, but since cracks can occur due to various factors other than the material's history, this method lacks reliability as a method for estimating history, and cannot be used in low stress ranges where cracks do not occur.
[0011] In Patent Document 2 and Non-Patent Document 1, it is verified that the twin density of calcite particles changes according to the magnitude of the external force applied to the measured object, and the stress history of the measured object is measured based on the result, but since the relationship between stress and twin density varies depending on the elastic modulus of the measured object, it is necessary to obtain a relationship between appropriate stress and twin density for each measured object. In addition, in Patent Document 3, a measured object in which a large number of calcite particles are embedded and which can be elastically deformed by receiving an external force is measured based on the ratio of calcite particles that have undergone twin deformation among the calcite particles embedded therein after receiving an external force, but in this case as well, it is necessary to obtain a relationship between appropriate stress and the ratio of calcite particles that have undergone twin deformation for each measured object. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] Patent No. 2876007 [Patent Document 2] JP 2008-286689 A [Patent Document 3] JP 2014-228511 A [Patent Document 4] International Publication No. 2012 / 108473 [Non-patent literature]
[0013] [Non-Patent Document 1] Sakaguchi et.al. “Elastic stress indication in elastically rebounded rock”, Geophysical Research Letters, vol. 38, L09316, doi:10. 1029 / 2011GL047055, 2011 Summary of the Invention [Problem to be solved by the invention]
[0014] It has been proposed to measure the stress history of a structural material such as concrete from the relationship between the stress due to an external force and the twin density (Patent Document 2), or the relationship between the stress due to an external force and the proportion of calcite particles in which twin deformation has occurred (Patent Document 3), but these methods cannot use the same relationship for structural materials with different elastic moduli.The present invention aims to provide a method for measuring stress history in a simple form that can be widely applied to various structural materials as long as the twin density and elastic modulus are known.
[0015] Another object of the present invention is to provide a method for removably embedding a plurality of calcite particles as stress sensors inside an object to be measured, extracting the embedded calcite particles from the object to be measured, and measuring the twin density of the extracted calcite particles, as well as examples of the shape of the plurality of calcite particles suitable for carrying out this method. [Means for solving the problem]
[0016] In order to achieve the above-mentioned object, the present invention provides a method for estimating the stress-strain history in a composite material mainly composed of cement, in which a plurality of calcite particles (11) having a predetermined particle diameter are embedded in a measured object (50) as stress sensors to estimate the stress-strain history of the measured object (50), characterized in that the plurality of calcite particles (11) are non-twinned calcite particles, mixed at a predetermined mixing ratio in a cement composite material (12) that has been pre-mixed so that the elastic modulus in a solidified state becomes a predetermined value, and the whole is formed into a calcite particle aggregate (10) having a predetermined shape, and one or more of the calcite particle aggregates (10) are embedded in the measured object (50) in a non-shrink mortar (60) or concrete structural material so as to be removably therefrom.
[0017] A second feature of the method for estimating stress-strain history in a composite material mainly composed of cement according to the present invention is that it is a method for estimating stress-strain history in a measured object (50) by embedding a plurality of calcite particles (11) having a predetermined particle diameter as stress sensors in the measured object (50) to estimate the stress-strain history of the measured object (50), the plurality of calcite particles (11) are non-twinned calcite particles, and are mixed at a predetermined mixing ratio in a non-shrink mortar (60) that has been mixed in advance so that the elastic modulus in a solidified state becomes a predetermined value, and are formed into a calcite particle aggregate (10') having fluidity, and the calcite particle aggregate (10') is embedded in the measured object (50) so as to be removably filled in a recess (51) provided in the measured object (50).
[0018] A third feature of the method of estimating the stress-strain history of a composite material mainly composed of cement according to the present invention is that the shape is a sphere, a polyhedron, or a flat plate.
[0019] A fourth feature of the method of estimating the stress-strain history in a cement-based composite material according to the present invention is that the calcite particles (11) contained in the calcite particle aggregates (10, 10') are colored.
[0020] A fifth feature of the method of estimating the stress-strain history in a cement-based composite material according to the present invention is that the surface of the calcite particle aggregate (10, 10') extracted from the object to be measured (50) is polished to such an extent that twin crystals of the calcite particles (11) can be observed.
[0021] A sixth feature of the method of estimating stress-strain history in a cement-based composite according to the present invention is to measure the twin density (Dtw) of the calcite particles on one or more surfaces of the polished calcite particle aggregates (10, 10').
[0022] A seventh feature of the method of estimating the stress-strain history in a composite material mainly composed of cement according to the present invention is that the relationship between the twin density (Dtw) of the calcite particles and the stress history (σ) generated in the measured object (50) is configured so as to have a one-to-one correspondence with each other for each elastic modulus of the cement composite (12) or the non-shrink mortar (60).
[0023] An eighth feature of the method for estimating the stress-strain history in a composite material mainly composed of cement according to the present invention is that, when the elastic modulus of the cement composite material (12) or the non-shrink mortar (60) is uniquely fixed, the relationship between the twin density (Dtw) of the calcite particles and the stress history (σ) is configured to be linearly approximated.
[0024] A ninth feature of the method for estimating the stress-strain history in a composite material mainly composed of cement according to the present invention is that, in converting the twin density (Dtw) of the calcite particles into the stress history (σ), an approximation formula is set for the strain (ε) generated in the measurement object (50) and a representative value of the twin density (Dtw) of the calcite particles. ε=0.0094Dtw-0.2 ………… (1) and further converting the strain (ε) into stress using the elastic modulus of the cement composite (12) or the non-shrink mortar (60), thereby estimating the stress history (σ) generated in the measurement object (50).
[0025] A tenth feature of the method for estimating stress-strain history in a cement-based composite material according to the present invention is that the calcite particle aggregates (10, 10') contain non-twinned synthetic calcite particles (11) having a particle diameter of 5 μm to 1.50 mm.
[0026] An eleventh feature of the method for estimating stress-strain history in a cement-based composite material according to the present invention is that the mixing ratio of the non-twinned synthetic calcite particles (11) in the calcite particle aggregate (10, 10') is 0.3 to 10 volume %.
[0027] The calcite particle aggregate (10, 10') according to the present invention for carrying out the method for estimating the stress-strain history in the composite material mainly composed of the above-mentioned cement is characterized in that a plurality of calcite particles (11) having a particle diameter of a predetermined size as a stress sensor are mixed and dispersed in a cement composite material (12) serving as a base material.
[0028] A second feature of the calcite particle aggregate (10) according to the present invention is that a plurality of calcite particles (11) serving as stress sensors having a particle diameter of a predetermined size are mixed and dispersed in a cement composite material (12) serving as a base material, and the whole has a predetermined shape.
[0029] A third feature of the calcite particle aggregate (10) according to the present invention is that the shape is a sphere, a polyhedron, or a plate.
[0030] A fourth feature of the calcite particle aggregates (10, 10') according to the present invention is that the calcite particles (11) are colored.
[0031] A fifth feature of the calcite particle aggregates (10, 10') according to the present invention is that they contain non-twinned synthetic calcite particles (11) having a particle diameter of 5 μm to 1.50 mm.
[0032] A sixth feature of the calcite particle aggregate (10, 10') according to the present invention is that the mixture ratio of the non-twinned synthetic calcite particles (11) is 0.3 to 10 volume %. Effect of the Invention
[0033] In the method of estimating the stress-strain history of the present invention, a large number of calcite particles are embedded as stress sensors, and for a composite material mainly made of cement that can elastically deform when subjected to an external force, the twin density of the calcite particles is measured after the composite material has been subjected to an external force, and the twin density is converted to strain using an approximation equation that represents the relationship between strain and twin density, and then the strain is converted to stress, making it possible to easily estimate the stress-strain history of the composite material in a common form regardless of the material.
[0034] In addition, in the stress-strain history estimation method of the present invention, a plurality of calcite particles as stress sensors are embedded inside the object to be measured in a removably manner, the embedded calcite particles are sampled from the object to be measured, and the twin density of the sampled calcite particles can be measured.
[0035] Furthermore, the calcite particle aggregate of the present invention makes it possible to suitably carry out the method of estimating the stress-strain history of a composite material mainly composed of cement of the present invention. [Brief description of the drawings]
[0036] [Figure 1] FIG. 1 is a diagram showing the relationship between stress and twin density for a number of composites containing calcite particles and having different elastic moduli, which was clarified as a premise for the method of the present invention. [Diagram 2] FIG. 1 shows the stress-twin density relationship for several composites containing calcite particles and having different elastic moduli, as demonstrated for application in the method of the present invention. [Diagram 3] This figure explains the concept of the method for measuring the stress-strain history of a composite that contains calcite particles as a stress sensor. (a) shows the state when no external force is applied, (b) shows the state when a compressive force is applied to the composite and the composite is undergoing compressive deformation, and (c) shows the state when the external force is removed and the composite is undergoing elastic recovery. [Figure 4] FIG. 1 is a flow diagram showing a procedure for embedding synthetic calcite particles in an existing structure. [Diagram 5]FIG. 2 is an explanatory diagram showing an example of the shape of a synthetic calcite particle aggregate according to the present invention. [Figure 6] FIG. 2 is a cross-sectional view of a main part showing an example of embedding synthetic calcite particle aggregates into an existing building, which is the object to be measured. [Figure 7] FIG. 1 is a flow diagram showing a procedure for embedding synthetic calcite particles into novel structures. [Figure 8] FIG. 2 is a flow diagram showing a procedure for harvesting synthetic calcite particle aggregates according to the present invention from an existing structure. [Figure 9] FIG. 1 is a cross-sectional view of a main portion showing an example of construction in which a portion of non-shrink mortar containing synthetic calcite particle aggregates is extracted from an existing building structure. [Figure 10] This is an explanatory cross-sectional view of an essential part showing a sampling core extracted from a structure, a synthetic calcite particle aggregate cut out from the sampling core, and a sampling core in which flat-plate-shaped synthetic calcite particle aggregates are embedded flush with the surface of the structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] Hereinafter, a method for estimating the stress-strain history in a structural material such as concrete according to one embodiment of the present invention will be described with reference to the attached drawings. The method for estimating the stress-strain history in a structural material such as concrete according to the present invention is common to the conventional techniques in Patent Document 2 and Non-Patent Document 1 in that calcite particles are contained in the structural material as stress sensors, and stress history is measured by focusing on the relationship between the stress generated by an external force applied to the structural material and the twin density in the calcite particles (hereinafter referred to as "calcite twin density"). However, the present invention improves the problems of these conventional techniques.
[0038] For example, in Non-Patent Document 1, it was found that the calcite twin density was proportional to the differential stress through compression tests on sandstone, but in the course of further investigation, it was found that the proportionality coefficient here includes elements related to strain and elastic modulus, and therefore it is thought that there remain problems as a realistic evaluation method. Furthermore, when the structural material is a composite material mainly made of cement, it is known that the elastic modulus changes depending on the cement-water ratio, and it is desirable to have a method of measuring stress history that can be applied to structural materials with different elastic moduli.
[0039] The concept of the method for measuring the stress history of a measurement object that contains calcite particles as stress sensors in its structural material is explained with reference to Figure 3. In each of Figures 3(a) to (c), the illustration on the left shows a partial cross section of a measurement object that contains a mixture of strong and weak particles, with stronger particles being darker and weaker particles being lighter, and the white particles are stress sensors that undergo plastic deformation due to stress. The illustration on the right shows roughly how the strong particles elastically support the overall load with connecting springs between the particles, and indicates the presence of a stress sensor between them.
[0040] Figure 3(a) shows a state where no external force is applied, and Figure 3(b) shows a state where a compressive force is applied to the measured object, causing the measured object to elastically deform in the compressive direction as a whole, and the stress sensor is also deformed. Figure 3(c) shows a state where the external force is removed, causing the measured object to elastically recover as a whole, and the stress and deformation disappear, but the stress sensor does not restore its shape and the stress history remains. Measurement of the stress history of the measured object is based on this concept. In calcite particles as a stress sensor, the deformation caused by the application of an external force causes the deformed crystal planes to appear as deformation twins between the simple crystal structures. The "calcite twin density" refers to the number of deformation twins per mm in the axial direction perpendicular to the e-plane where twins are generated.
[0041] The magnitude of deformation of the object to be measured when subjected to an external force in the compressive direction depends on the elastic modulus of the object as a whole, which corresponds to the strength of the spring that connects the frames of hard particles in each of the right-hand diagrams of Figures 3(a) to (c). In other words, the twin deformation remaining in the calcite particles as a stress sensor will differ depending on the strength of this spring. Therefore, if the elastic modulus of the object to be measured differs, it is considered that the relationship between stress and twin deformation when subjected to an external force will also differ. In Non-Patent Document 1, a relationship between the change in calcite twin density and stress is obtained for sandstone, but it is considered that this relationship cannot be said to apply to, for example, structural materials made of cement. Therefore, in the present invention, we are studying from the viewpoint of obtaining a relationship that is appropriate when measuring the stress history of a wider range of structural materials.
[0042] The composite to be measured contains many calcite particles, and these calcite particles are synthetic calcite particles. Most natural calcite particles have particle sizes that are too small compared to synthetic ones, making it impossible to determine stress. In addition, there are virtually no natural calcite particles that are twin-free, so they are not suitable for the method of estimating the stress-strain history of structural materials such as concrete according to the present invention. Therefore, the method of estimating the stress-strain history of structural materials such as concrete according to the present invention requires the use of synthetic calcite particles. These synthetic calcite particles are synthesized by the method of producing single crystal calcite as shown in Patent Document 4.
[0043] In the present invention, the synthetic calcite particles contained in the composite have the following conditions. (a) Size of synthetic calcite particles The shape of the synthetic calcite crystal is a parallelepiped, and the particle size is represented by the short side. If the particle size is too small, it becomes difficult to detect, and if it is too large, it affects the strength of the composite, so the particle size is preferably in the range of 5 μm (0.005 mm) to 1.50 mm, more preferably 0.01 to 1.20 mm, and even more preferably 0.1 to 1.0 mm. (b) Mixing ratio of synthetic calcite particles In order to make the particles easier to detect without reducing the strength of the composite, the mixing ratio of the synthetic calcite particles in the composite is preferably 0.3 to 10 volume %, and more preferably 1 to 5 volume %.
[0044] [Verification of the relationship between stress and twin density using elastic modulus] The relationship between the stress caused by compressive load and the twin density of calcite particles in the test objects made of cement with different elastic moduli was obtained and compared. A specific ratio of calcite particles was mixed into the cement-based structural material of each test object for which the relationship between stress and twin density was obtained. The calcite particles were synthesized as follows.
[0045] [A] Synthesis of calcite particles The synthesis of calcite particles was in accordance with the method described in Patent Document 4, and was carried out in the following steps. (1) 5M ammonium adjustment Four 1-L beakers were prepared, and 400.2 g of ammonium nitrate was added to each, followed by 1 L of water. The beakers were heated with a magnetic stirrer and mixed until the mixture became transparent. (2)pH adjustment The pH of the solution mixed in (1) was adjusted to 7.50 just before reaction. Ammonia was added to raise the pH. (3) Reaction preparation Put 4 L of the pH-adjusted solution into a container. Add 36 g (9 g / L) of calcium carbonate to it. Attach a Teflon (registered trademark) handle and place it in an autoclave. (4) Autoclave operation The autoclave operation was carried out with a program that increased the temperature to 180°C, held it at 180°C for 12 hours, and decreased it to 30°C in 60 hours. (5) Post-treatment / filtration After the autoclave operation, the resulting slurry was subjected to suction filtration to obtain synthetic calcite.
[0046] [B] Formation and testing of the object to be measured Using cement for high-strength concrete, three types of test specimens were prepared with cement to water ratios of standard amount / 1.5 times standard amount / 2 times standard amount. Each of these has a different elastic modulus depending on the water ratio, and there are three types based on the average elastic modulus E: hard cement (E: 10.1 GPa), medium cement (E: 8.6 GPa), and weak cement (E: 5.9 MPa).
[0047] Synthetic calcite particles with particle diameters of 0.2 to 0.5 mm were mixed into each cement to be measured at a ratio of 1 to 5% by volume, and after 4 weeks of curing, the mixture was molded into a diameter of 20 mm and a length of approximately 40 mm, and a compression test was performed. The test was performed under atmospheric pressure using a UH-1000kN type testing machine (manufactured by Shimadzu Corporation), and stresses ranging from low stress to destructive stress were applied. The samples were then cut into thin slices, and the twin density of several dozen or more calcite particles was measured using a polarizing microscope. This measurement involved scanning the entire surface to be inspected with a polarizing microscope, and calculating a representative value of the twin density for multiple calcite particles for which the presence or absence of twins could be confirmed. The twin density of each sample containing multiple calcite particles was determined to be the most frequent value of the frequency distribution, which was taken as the representative value of the twin density.
[0048] The relationship between the applied stress and the twin density generated for each of the three types of cement measured is shown in Figure 1. Figure 1 also shows the measurement results for sandstone. As can be seen from the results in Figure 1, the relationship between the stress and twin density of the measured objects is expressed by a linear equation for each material, but these equations differ depending on the elastic modulus of the material. In other words, to convert twin density to stress, it is necessary to determine the equation for each material.
[0049] On the other hand, the relationship between the strain and twin density when a load is applied to each measured object is shown in Figure 2. As can be seen from Figure 2, the strain ε (%)-twin density Dtw (twins / mm) of the measured objects for each cement, including sandstone, is distributed in a way that is represented by a common straight line. This straight line is, ε=0.0094Dtw-0.2 ……… (1) The twin density Dtw is expressed as the most frequent value of the frequency distribution as a representative value of the twin density. In Figures 1 and 2, the horizontal axis Dtw indicates the representative value of this twin density (twin / mm).
[0050] In this way, in the stress-twin density relationship shown in Figure 1, the approximation formula that expresses the relationship varies depending on the material and elastic modulus of the measured object, whereas the strain-twin density relationship shown in Figure 2 can be expressed by one common approximation formula (1) regardless of the material and elastic modulus of the measured object.
[0051] In the previous method described in Non-Patent Document 1, stress is estimated by converting the stress and twin density of calcite particles into stress, but this conversion formula differs depending on the material of the object being measured, so it cannot be done in a common form. However, if twin density is converted into strain using the approximate formula (1) that expresses the relationship between strain and twin density, it can be done in a common form regardless of the material. On top of that, the relationship between stress (σ), strain (ε), and elastic modulus (E) σ=εE ………… (2) From this, the strain can be converted into stress, and the stress can be estimated.
[0052] In the method for estimating stress and strain according to the present invention, it is possible to estimate the stress generated in a composite material by simply adding synthetic calcite particles to the composite material mainly made of cement and measuring the twin density of the calcite particles. In the conventional method of attaching an electrical sensor to a composite material, the sensor becomes a foreign body in the composite material and inevitably affects its mechanical properties, but the calcite particles mixed in the present invention are originally present in the cement and do not become a foreign body when added in small amounts. [Industrial Applicability]
[0053] The method for estimating stress-strain history according to the present invention can be effectively applied to cases where equipment or structures that are constantly subjected to stress are inspected to determine whether they maintain a specified strength after being subjected to an action such as an earthquake that is not destructive, or whether the structure itself has deteriorated, and where local stress concentrations due to deterioration of equipment or structures are monitored.
[0054] As described above, the method for estimating the stress-strain history of a composite material mainly made of cement according to the present invention has been shown to be capable of quantitatively estimating the stress-strain history of an object to be measured by measuring the twin density Dtw of synthetic calcite particles contained in the object to be measured after an external force has been applied. In the following, we will explain the embedding of synthetic calcite particles as a stress sensor into a cement-based structure (concrete structural material) as the object to be measured, the collection (recovery) of the embedded synthetic calcite particles from the structure for measuring the twin density Dtw, and the measurement of the twin density of the collected synthetic calcite particles.
[0055] [Embedding synthetic calcite particles into structures] FIG. 4 is a flow diagram showing the procedure for embedding synthetic calcite particles into an existing structure. First, in step P1, a synthetic calcite particle aggregate 10 is produced. The synthetic calcite particle aggregate 10 referred to here is a composite in which a large number (plurality) of synthetic calcite particles 11 as stress sensors are mixed into a cement composite material 12 as a base material, and the whole is solidified into a predetermined shape, as shown in Fig. 5. The cement composite material 12 as a base material (solid agent) is a composite material mainly made of cement that can be elastically deformed when subjected to an external force, and specifically corresponds to a composite material mainly made of cement with a known average elastic modulus E, such as hard cement (E: 10.1 GPa), medium cement (E: 8.6 GPa), or weak cement (E: 5.9 MPa), which is created by changing the ratio of cement to water in the above-mentioned "(B) Formation and testing of the measurement target object".
[0056] In addition to the mixture of cement and water, mortar can also be used as the cement composite material 12. In this case, the ratio of cement to sand in the mortar is, for example, 1:2 by mass, and the elastic modulus is adjusted by the amount of water. Synthetic calcite particles 11 with a particle size of, for example, 0.2 to 0.5 mm are mixed into the mortar mixed to a predetermined elastic modulus, so that the content is, for example, 1 to 5 volume %.
[0057] The synthetic calcite particles 11 contained in the synthetic calcite particle aggregate 10 are non-twinned synthetic calcite particles. The non-twinned synthetic calcite particles 11 can be synthesized by the above-mentioned "(A) Synthesis of Calcite Particles". By using the non-twinned synthetic calcite particles 11, the initial value of the twin density Dtw of the synthetic calcite particles becomes zero, which makes it easier to estimate the stress history generated in the measurement object (step P4 in FIG. 8), which will be described later.
[0058] When the cement composite 12 is mortar, the particle diameter (grain size) of the synthetic calcite particles 11 is preferably the same as the grain size of the sand as the aggregate constituting the mortar, specifically, for example, 63 μm (0.063 mm) to 2000 μm (= 2 mm). In addition, the "particle diameter of the synthetic calcite particles" referred to in this specification refers to the minor axis of a rectangle circumscribing the maximum projection surface. If the grain size of the synthetic calcite particles 11 is too large, the synthetic calcite particle aggregate 10 obtained is likely to not have sufficient strength as required, while if the grain size of the synthetic calcite particles 11 is too small, it becomes difficult to measure the twin density Dtw of the synthetic calcite particles on the crystal plane.
[0059] The content of the synthetic calcite particles 11 in the synthetic calcite particle aggregate 10 is preferably, for example, 0.3 to 10 volume %, and more preferably 1 to 5 volume %, which makes it possible to reliably prevent a decrease in the strength of the resulting synthetic calcite particle aggregate 10 while reliably carrying out the intended stress measurement (inspection).
[0060] Fig. 5(a) shows a synthetic calcite particle aggregate 10 formed into a sphere. Fig. 5(b) shows a synthetic calcite particle aggregate 10 formed into a cube. Fig. 5(c) shows a synthetic calcite particle aggregate 10 formed into a plate. By using the synthetic calcite particle aggregate 10, it is possible to secure the number of synthetic calcite particles required for measuring the twin density Dtw of the synthetic calcite particles on the inspection surface. An example of a method for forming the synthetic calcite particle aggregate 10 will be described below.
[0061] [Method for forming synthetic calcite particle aggregate 10] For example, when the finished shape is a sphere, synthetic calcite particles 11 with a particle diameter of 0.2 to 0.5 mm are mixed into the cement composite material 12 so as to have a content ratio of 1 to 5 volume %, and this mixture is placed in a mold having a spherical recess (cavity) and cured for a predetermined time (for example, 4 weeks), thereby forming a spherical synthetic calcite particle aggregate 10. Therefore, by changing the mold, it is possible to suitably form synthetic calcite particle aggregates 10 having shapes other than a sphere. Note that the synthetic calcite particles 11 may be colored with a reagent such as anizarin red before being mixed into the cement composite material 12 so that the occurrence of twin deformation can be easily detected in the measurement of the twin density Dtw during stress estimation.
[0062] The synthetic calcite particle aggregate 10 has a maximum outer diameter of, for example, about 10 to 50 mm when finished. The finished size varies depending on the size of the bottomed hole 51, which will be described later.
[0063] 4, step P2 is to select a location for embedding the synthetic calcite particle aggregates 10. It is preferable to select a location for embedding the synthetic calcite particle aggregates 10 into the existing structure 50 at a location where stress is concentrated in terms of design.
[0064] In step P3, a bottomed hole 51 for embedding the synthetic calcite particle aggregate 10 is formed in the selected embedding location (FIG. 6(a)). The shape and size of the bottomed hole 51 are such that they do not affect the strength of the structure 50. For example, for a synthetic calcite particle aggregate 10 with a maximum outer diameter of about 10 to 50 mm, a cylindrical bottomed hole with a diameter of 120 mm and a depth of 60 mm can be formed.
[0065] In step P4, the synthetic calcite particle aggregate 10 is embedded in the bottomed hole 51 using non-shrink mortar 60 (FIG. 6(b)). Specifically, the synthetic calcite particle aggregate 10 is mixed in while backfilling the bottomed hole 51 with the non-shrink mortar 60.
[0066] In step P5, an embedding location marking 70 is made at the embedding location of the synthetic calcite particle aggregate 10 (FIG. 6(d)). The embedding location marking 70 can be made, for example, at the center of the bottomed hole 51. In addition, the size of the bottomed hole 51 (Φ120×60), the date when the synthetic calcite particle aggregate 10 was embedded in the structure 50, etc. can be added.
[0067] The above is the procedure for embedding the synthetic calcite particles 11 in the existing structure 50 using the synthetic calcite particle aggregate 10. However, it is also possible to embed the synthetic calcite particles 11 in the existing structure 50 without using the synthetic calcite particle aggregate 10.
[0068] As shown in Figure 6 (c), when synthetic calcite particle aggregates 10 are not used, synthetic calcite particles 11 can be embedded in an existing structure 50 by mixing synthetic calcite particles 11 into non-shrink mortar 60 so that the content ratio is, for example, 1 volume %, and then backfilling the bottomed hole 51 with a mixture of synthetic calcite and mortar (synthetic calcite aggregates 10') that has been pre-mixed by adding water to obtain a predetermined elastic modulus.
[0069] Also, as shown in Fig. 7, the procedure for embedding synthetic calcite particles in a new structure is to "inject synthetic calcite particle aggregates 10 into the designed stress concentration points when pouring concrete" instead of steps P3 and P4 in Fig. 4. Next, the procedure for extracting the synthetic calcite particle aggregates 10 embedded in the structure 50 will be described.
[0070] 8 is a flow diagram showing the extraction of the synthetic calcite particle aggregate 10 from the building 50 and the estimation of the stress history. For the convenience of explanation, it is assumed that the synthetic calcite particle 11 is embedded in the building 50 in the form of the synthetic calcite particle aggregate 10. First, in step P1, a portion of the non-shrink mortar 60 containing a plurality of synthetic calcite particle aggregates 10 is extracted from the existing building 50. The extraction can be performed, for example, by using a commercially available core drill 200 (FIG. 9) for concrete structural materials to extract the portion of the non-shrink mortar 60 in the form of a core. The extraction of the embedded portion of the synthetic calcite particle aggregates 10 using the core drill 200 will be briefly described below.
[0071] As shown in Fig. 9(a), the core drill 200 (the motor that rotates the core drill 200 is not shown) is provided with a circumferential blade 210 at the tip of a hollow cylindrical body, and a center drill 220 on the central axis inside the body. The circumferential blade 210 and the center drill 220 rotate together. The circumferential blade 210 is for cutting the structure 50 into a core shape, and the center drill 220 is for screwing into the sampling core cut into a core shape to capture the sampling core in the core drill 200.
[0072] First, for example, the core drill 200 is positioned so that the embedding location mark 70 of the synthetic calcite particles is located on the central axis of the center drill 220. While maintaining the relative positional relationship between the embedding location mark 70 and the center drill 220, the core drill 200 is rotated and moved forward toward the building 50.
[0073] As shown in FIG. 9( b ), the core drill 200 is rotated and penetrated to a predetermined depth into the structure 50 until a plurality of synthetic calcite particle aggregates 10 are captured inside the core drill 200 .
[0074] 9(c), when the core drill 200 penetrates to a predetermined depth into the building 50, the rotation of the core drill 200 is stopped and moved in the reverse direction. In this case, since the center drill 220 is screwed into the part 50' of the building from which the synthetic calcite particle aggregate 10 was extracted and the part 60' of the non-shrinkage mortar, the core drill 200 is moved in the reverse direction without rotating, so that the embedded part of the synthetic calcite particle aggregate 10 can be extracted from the building 50.
[0075] Returning to Fig. 8, in step P2, the synthetic calcite particle aggregate 10 is cut out from the sampling core 100 extracted from the building 50. As shown in Fig. 10(a), the sampling core 100 extracted from the building 50 is composed of a portion 60' of non-shrink mortar containing the synthetic calcite particle aggregate 10 and a portion 50' of the building.
[0076] As shown in Fig. 10(b), the non-shrink mortar portion 60' and further the synthetic calcite particle aggregate 10 are cut out to expose the crystal faces of the multiple synthetic calcite particles 11. The cut surface of the synthetic calcite particle aggregate 10 where the crystal faces of the synthetic calcite particles 11 are exposed becomes the inspection surface. The size of the inspection surface can be appropriately set depending on the purpose.
[0077] As shown in Fig. 10(c), when the flat synthetic calcite particle aggregate 10 is embedded flush with or slightly shallower than the surface (wall) of the building 50, there is no need to cut out the synthetic calcite particle aggregate 10 from the collected core 100, and the crystal faces of the multiple synthetic calcite particles 11 can be suitably exposed by polishing the surface to an extent that does not affect the strength of the object to be measured itself. In addition, since the measurement can be performed non-destructively, it is also possible to perform continuous observations, such as comparisons of aging changes and before and after the occurrence of accidents.
[0078] Returning to FIG. 8, in step P3, the twin density is measured for a plurality of synthetic calcite particles 11 whose crystal faces are exposed on the inspection surface. As described above, the "twin density of synthetic calcite particles" is defined by the number of twins contained per a predetermined length (e.g., 1 mm) in the axial direction perpendicular to the e-plane along which twins are generated, so it is necessary to measure the number of twins for each of the plurality of synthetic calcite particles 11 whose crystals are exposed on the inspection surface. The number of twins is measured, for example, by scanning the entire inspection surface with an optical microscope and performing image analysis on the synthetic calcite particles 11 whose crystal faces are exposed. That is, since the refractive index or reflectance changes with the deformation of the crystal lattice of the synthetic calcite particles 11, the presence or absence of twins in the synthetic calcite particles 11 can be easily determined by analyzing the change in the refractive index or reflectance. Thereby, the number of twins contained per a predetermined length (e.g., 1 mm) in the axial direction perpendicular to the e-plane along which twins are generated is measured for each of the plurality of synthetic calcite particles 11 whose crystal faces are exposed. The average value of the number of twins contained per predetermined length measured is the twin density Dtw of the synthetic calcite.
[0079] Next, in step P4, the stress history generated in the measured object is estimated. As described above, the average twin density Dtw of a plurality of synthetic calcite particles present in an inspection target area of a predetermined size depends on the magnitude of the external force, and the average twin density of the synthetic calcite particles tends to increase as the external force increases, specifically, the average twin density Dtw of the synthetic calcite particles is in a proportional relationship with the magnitude of the external force, so that the history of the stress generated in the measured object (the structure 50) can be estimated based on the degree of change in the obtained average twin density Dtw from the initial value (e.g., 0).
[0080] Therefore, for example, when the elastic modulus E of the cement composite material 12 of the synthetic calcite particle aggregate 10 is adjusted to 10.1 GPa, by substituting the twin density Dtw of the synthetic calcite particles measured in the above procedure P3 into the relational expression of stress-calcite twin density for the hard cement E: 10.1 GPa in FIG. 1, the history of the stress σ generated in the object to be measured (building 50) can be estimated.
[0081] By the way, although the elastic modulus E of the cement composite material 12 is known, when there is no relational expression (linear approximation expression) of stress-calcite twin density in FIG. 1 (for example, when 10.1 GPa < E < 29.3 GPa), by substituting the twin density Dtw of the synthetic calcite particles measured in the above procedure P3 into the relational expression of strain-calcite twin density of the above (1) shown in FIG. 2, the strain history ε generated in the object to be measured (building 50) is estimated, and then by multiplying the estimated strain history ε by the elastic modulus E of the cement composite material 12, the stress history σ generated in the object to be measured (building 50) can be estimated.
[0082] Regarding the embedded synthetic calcite particle aggregate 10' (FIG. 6(c)), by following the above collection procedure of the synthetic calcite particles and the measurement procedure of the twin density Dtw of the synthetic calcite particles for the collected core shown in FIG. 8, it can be suitably recovered from the building 50, and the stress history generated in the building 50 can be suitably estimated.
[0083] As described above, according to the method of estimating stress-strain history in a composite material mainly made of cement according to the present invention, a plurality of synthetic calcite particles 11 are non-twinned calcite particles, which are mixed in a predetermined mixing ratio in a cement composite material 12 that is prepared in advance so that the elastic modulus in a solidified state is a predetermined value, and the whole is formed into a predetermined shape (for example, a sphere, a polyhedron, a flat plate) to form a calcite particle aggregate 10. Then, one or a plurality of the calcite particle aggregates 10 are embedded in a structure 50 using non-shrink mortar 60 or a concrete structural material so that they can be removably embedded. This makes it easy to embed the synthetic calcite particles 11 as stress sensors in the structure 50 and to extract (recover) them from the structure 50, and also makes it easy to measure the twin density Dtw of the recovered synthetic calcite particles.
[0084] In addition, even when a plurality of non-twinned synthetic calcite particles 11 are mixed at a predetermined mixing ratio in a non-shrinkage mortar 60 that has been prepared in advance so that the elastic modulus in the solidified state becomes a predetermined value, and a fluid calcite particle aggregate 10' is formed, and the aggregate is filled into a bottomed hole 51 provided in the structure 50 and embedded in the structure 50 so that it can be removed, the synthetic calcite particles 11 as stress sensors can be easily embedded in the structure 50 and extracted (recovered) from the structure 50, and the twin density Dtw of the recovered synthetic calcite particles can be easily measured.
[0085] When the synthetic calcite particles 11 are colored with a reagent such as anizarin red, it becomes easy to confirm the presence or absence of twins in the synthetic calcite particles 11 whose crystal faces are exposed on the inspection surface.
[0086] Moreover, according to the method of estimating the stress-strain history in a composite material mainly composed of cement according to the present invention, the relationship between the twin density Dtw of the synthetic calcite particles and the stress history σ generated in the building 50 is configured to be linearly approximated for each elastic modulus of the cement composite 12 or the non-shrink mortar 60. Therefore, it becomes possible to uniquely estimate the stress history σ generated in the building 50 from the measured twin density Dtw of the synthetic calcite particles.
[0087] Furthermore, the relationship between the twin density Dtw of the synthetic calcite particles and the strain history ε occurring in the structure 50 is configured to be linearly approximated, independent of the elastic modulus of the cement composite 12 or the non-shrink mortar 60. Therefore, even if the elastic modulus E of the cement composite 12 or the non-shrink mortar 60 is known, but the relationship between the twin density Dtw of the synthetic calcite particles and the stress history σ occurring in the structure 50 is not configured to be linearly approximated, it is possible to uniquely estimate the strain history ε occurring in the structure 50 from the measured twin density Dtw of the synthetic calcite particles. Then, by multiplying the estimated strain history ε by the known elastic modulus E, it is possible to uniquely estimate the stress history σ occurring in the structure 50. Explanation of symbols
[0088] 10 Synthetic calcite particle aggregates 10' Synthetic calcite particle aggregate 11 Synthetic calcite particles 12 Cement composites 50 Buildings (objects to be measured) 50' Building Part 51 Bottomed hole (dent) 52 Drilling 60 Non-shrink mortar 60' Non-shrink mortar section 70 Burial site mark 100 Harvesting Cores 200 Core Drill 210 Circumferential blade 220 Center Drill
Claims
1. A method for estimating a stress / strain history, comprising embedding a plurality of calcite particles (11) having a predetermined particle diameter in a measured object (50) as a stress sensor to estimate a stress / strain history of the measured object (50), comprising: The plurality of calcite particles (11) are non-twinned calcite particles, which are mixed in a predetermined mixing ratio into a cement composite material (12) which has been mixed in advance so that the elastic modulus in a solidified state is a predetermined value, and the whole is formed into a predetermined shape to form a calcite particle aggregate (10); One or more of the calcite particle aggregates (10) are removably embedded in the object to be measured (50) using non-shrink mortar (60) or concrete construction material. A method for estimating the stress and strain history in a cement-based composite material, comprising:
2. A method for estimating a stress / strain history, comprising embedding a plurality of calcite particles (11) having a predetermined particle diameter in a measured object (50) as a stress sensor to estimate a stress / strain history of the measured object (50), comprising: The plurality of calcite particles (11) are non-twinned calcite particles, and are mixed at a predetermined mixing ratio in a non-shrinkage mortar (60) that has been premixed so that the elastic modulus in a solidified state is a predetermined value, and are formed into a calcite particle aggregate (10') having fluidity; The calcite particle aggregate (10') is embedded in the object to be measured (50) so as to be removably disposed therein while filling a recess (51) formed in the object to be measured (50). A method for estimating the stress and strain history in a cement-based composite material, comprising:
3. The shape is a sphere, a polyhedron, or a plate.
2. A method for estimating stress-strain history in a cement-based composite material according to claim 1.
4. The calcite particles (11) contained in the calcite particle aggregates (10, 10') are colored. A method for estimating stress-strain history in a composite material mainly composed of cement according to any one of claims 1 to 3.
5. The surface of the calcite particle aggregate (10, 10') taken out of the measurement object (50) is polished to such an extent that twin crystals of the calcite particles (11) can be observed. A method for estimating stress-strain history in a composite material mainly composed of cement according to any one of claims 1 to 4.
6. The twin density (Dtw) of the calcite grains is measured on one or more surfaces of the polished calcite grain aggregate (10, 10').
6. A method for estimating stress-strain history in a cement-based composite material according to claim 5.
7. The relationship between the twin density (Dtw) of the calcite particles and the stress history (σ) generated in the measurement object (50) is configured to correspond one-to-one to each other for each elastic modulus of the cement composite material (12) or the non-shrink mortar (60).
7. A method for estimating stress-strain history in a cement-based composite material according to claim 6.
8. When the elastic modulus of the cement composite (12) or the non-shrink mortar (60) is uniquely fixed, the relationship between the twin density (Dtw) of the calcite particles and the stress history (σ) is configured to be linearly approximated.
8. A method for estimating stress-strain history in a composite material mainly composed of cement according to claim 6 or 7.
9. In converting the twin density (Dtw) of the calcite particles into the stress history (σ), an approximation formula is set for the strain (ε) generated in the measured object (50) and the representative value of the twin density (Dtw) of the calcite particles. ε=0.0094Dtw-0.2 ……(1) The measured twin density (Dtw) of the calcite particles is converted into strain (ε) using the elastic modulus of the cement composite material (12) or the non-shrink mortar (60), and the strain (ε) is converted into stress to estimate the stress history (σ) generated in the measurement object (50). A method for estimating stress-strain history in a cement-based composite material according to any one of claims 6 to 9.
10. The calcite particle aggregates (10, 10') contain twin-free synthetic calcite particles (11) having a particle size of 5μ to 1.50 mm. A method for estimating stress-strain history in a cement-based composite material according to any one of claims 1 to 9.
11. The mixture ratio of the non-twinned synthetic calcite particles (11) in the calcite particle aggregate (10, 10') is 0.3 to 10 volume %. A method for estimating stress-strain history in a cement-based composite material according to any one of claims 1 to 10.
12. A plurality of calcite particles (11) serving as stress sensors having a particle diameter of a predetermined size are colored, mixed and dispersed in a cement composite material (12) serving as a base material that has been premixed so that the elastic modulus in a solidified state is a predetermined value, and the whole is molded into a predetermined shape, so that it can be embedded in and removed from an object to be measured (50). A calcite particle aggregate characterized in that
13. The shape is a sphere, a polyhedron, or a plate.
13. The calcite particle aggregate of claim 12.
14. The present invention includes synthetic calcite particles (11) having a particle size of 5 μm to 1.50 mm.
13. The calcite particle aggregate of claim 12.
15. The mixing ratio of the non-twinned synthetic calcite particles (11) is 0.3 to 10 volume %.
15. The calcite particle aggregate of claim 14.
Citation Information
Patent Citations
Stress hysteresis measuring method, and composite material comprising mainly cement
JP2008286689A
Stress history measurement method and stress sensor
JP2014228511A
Method for measuring stress history of concrete structures
JP2876007B1
Method of determining stress history and composite material obtained mainly from cement
WO2010055584A1
Method for producing calcite single crystal
WO2012108473A1